Sex differences in torpor patterns during natural hibernation in golden-mantled ground squirrels (Callospermophilus lateralis) - Healy, Jessica E.; Burdett, Kendra A.; Buck, C. Loren; Florant, Gregory L. (Journal of mammalogy, 2012)
Golden-mantled ground squirrels (Callospermophilus lateralis) have been subjects of laboratory investigations of hibernation for many years. As such, patterns of torpor for this species have been well characterized under laboratory conditions but not during natural hibernation. The purpose of this study was to determine torpor patterns of free-living C. lateralis and to correlate these patterns with the sex, age, and reproductive status of each animal, as well as environmental conditions. We surgically implanted body temperature (Tb) data loggers into the abdominal cavities of animals in late summer 2008 and 2009. In spring 2009 and 2010, animals were recaptured and loggers were removed. During hibernation, animals displayed mean (± SEM) torpor bout lengths from 8 to 14 (± 0.3) days with maximum duration of 21 days, and minimum Tb of 0°C ± 1°C. Adult males entered hibernation later, emerged earlier, spent less time in torpor, and had fewer multiday torpor bouts than either females or juvenile males. These results suggest that torpor patterns in naturally hibernating C. lateralis are influenced by sex and reproductive status.